Ultraviolet Light in Water and Wastewater Sanitation - Masschelein, Willy J (CRC Press, 2009)
Several general books are available on ultraviolet light and its applications. However, this is the first comprehensive monograph that deals with its application to water and wastewater treatment. There is a rapidly growing interest in using UV light in water sanitation due to the increased knowledge of the potential health and environmental impacts of disinfection byproducts.